The liquid enemy: discursive construction of the political enemy in 2018 Costa Rica's presidential campaign - Ureña-García, Óscar (2023)
Building a solid enemy in the electoral campaign has been a frequent task. However, that construction has evolved towards a more liquid enemy, whichis molded according to the container in which it needs to be located. This paper is an analysis of the discursive construction of the political enemy inCosta Rica's presidential campaign in 2018 and in how the candidate Fabricio Alvarado constructed his adversary.